Practicing degree of problem- solving skills and their relationship to the academic achievement of fourth- grade students in the schools of the Syrian city of Hama - Al- Omari, Mai Azzam; Farha, Fatima Youssef; Shaaban, Amna Hashem (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at determining The practicing degree of problem- solving skills and their relationship to the academic achievement of fourth- grade students in the schools of the Syrian city of Hama The study adopted the descriptive- analytical approach. It used a questionnaire consisting of (31) items distributed on four axes: (defining the problem- determining the reasons- proposing solutions- Choosing the best solution), the research was applied to (376) students of the fourth grade, and due to the specificity of the questionnaire items, it was applied to teachers so that each teacher answered only two of his students, who were randomly identified By the researcher. The study Showed That: The degree of practicing problem- solving skills among fourth- grade students in the city of Hama came to a medium degree and an arithmetic mean of (1.80), and the axis (application and generalization of solutions) came in the first place and an average degree with an arithmetic average of (2.11), followed by the axis (identifying the reasons) in The second rank was at a medium degree, with an average score of (2.06), then the (defining the problem) axis came in the third rank with an average degree and an arithmetic average of 1.99, while the (proposing solutions) axis came in the last rank with a medium degree with an arithmetic mean of (1.96). and There is no statistically significant relationship between practicing degree of problem- solving skills for fourth- grade students and academic achievement, the researchers suggested the necessity of conducting tests to measure problem solving skills for different levels of education and their relationship to other variables.